Oil price shocks and the composition of current account balance - Serdar Varlik; Hakan Berument (Central Bank Review (CBR), 2020)
It is a well-established regularity that permanent oil price shocks do not have a permanent effect on the current account deficit. This requires that sub-components of the current account or trade balance will make the necessary adjustments to accommodate the higher energy bill of a country triggered by permanent crude oil price increases. Empirical evidence gathered from Turkey reveals that, in the long run, balancing the current account is provided by a permanent increase in the net exports of Agricultural Production, Maintenance and Repair Services, Travel, Construction, Financial Services, Compensation of Employees, and Goods under Merchanting (non-tradable components of the current account balance); and a permanent decrease in the net exports of Mining, Fishery, Other Goods for BEC Classification, Investment Income, Manufacturing Services on Physical Inputs Owned by Others, and Transport balances mostly in sectors that use energy heavily in production. All these responses are found to be statistically significant in the more than 24 periods we consider in this study.
Keywords: F14; F17; Q40; 330; Oil prices; Current account balance; FAVAR